Drug-induced liver injury: Advances and confusions in treatment - CHEN Shuai (Editorial Department of Journal of Clinical Hepatology, 2021)
Drug-induced liver injury (DILI) is one of the most common and serious adverse drug reactions and can lead to acute liver failure and even death in severe cases. The pathogenesis of DILI has not been fully clarified, and there is significant individual difference. There is no effective treatment for advanced DILI except liver transplantation, and therefore, early diagnosis and precise treatment are of particular importance. This article reviews the important research advances and difficult issues in the treatment of DILI in recent years.